Thermodynamic, Anticoagulant, and Antiproliferative Properties of Thrombin Binding Aptamer Containing Novel UNA Derivative - Weronika Kotkowiak; Jolanta Lisowiec-Wachnicka; Jakub Grynda; Ryszard Kierzek; Jesper Wengel; Anna Pasternak (Elsevier, 2018)
Thrombin is a serine protease that plays a crucial role in hemostasis, fibrinolysis, cell proliferation, and migration. Thrombin binding aptamer (TBA) is able to inhibit the activity of thrombin molecule via binding to its exosite I. This 15-nt DNA oligonucleotide forms an intramolecular, antiparallel G-quadruplex structure with a chair-like conformation. In this paper, we report on our investigations on the influence of certain modified nucleotide residues on thermodynamic stability, folding topology, and biological properties of TBA variants. In particular, the effect of single incorporation of a novel 4-thiouracil derivative of unlocked nucleic acid (UNA), as well as single incorporation of 4-thiouridine and all four canonical UNAs, was evaluated. The studies presented herein have shown that 4-thiouridine in RNA and UNA series, as well as all four canonical UNAs, can efficiently modulate G-quadruplex thermodynamic and biological stability, and that the effect is strongly position dependent. Interestingly, TBA variants containing the modified nucleotide residues are characterized by unchanged folding topology. Thrombin time assay revealed that incorporation of certain UNA residues may improve G-quadruplex anticoagulant properties. Noteworthy, some TBA variants, characterized by decreased ability to inhibit thrombin activity, possess significant antiproliferative properties reducing the viability of the HeLa cell line even by 95% at 10 μM concentration.